Geopolitical Shifts, Global Crises, and Renewable Trends Reshaping Oil and Gas: Pergeseran Geopolitik, Krisis Global, dan Tren Energi Terbarukan yang Mengubah Wajah Industri Minyak dan Gas - Kudratkhodjaeva Ziyoda Kamol kizi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Energy security is a cornerstone of national stability and global economic resilience. Specific Background: Recent wars, crises, and shifting alliances have exposed the fragility of fossil fuel dependence while accelerating renewable transitions. Knowledge Gap: Few studies integrate the impacts of crises, geopolitics, and renewable trends on oil and gas production. Aims: This paper analyzes how geopolitical disruptions, economic shocks, and renewable investments shape global energy security. Results: The findings show that traditional strategies of domestic production and supply diversification alone are insufficient, as crises disrupt infrastructure, markets, and investments. Meanwhile, renewable expansion in the EU, US, and China strengthens resilience and redefines energy autonomy. Novelty: The study offers an integrated framework linking geopolitical leverage, crisis vulnerabilities, and renewable transitions. Implications: Effective energy security requires combining fossil fuel management with renewable strategies, innovation, and international cooperation to reduce volatility and align with climate goals.Highlight : Energy security is influenced by global crises and geopolitical changes. Fossil fuel dependency creates risks that renewables can help reduce. Policies must balance national security with sustainability goals. Keywords : Energy, Economic Stability, Oil and Gas, Geopolitical Panorama, Fossil Fuels